Synergy of Scientific Literacy and Wasathiyah Values in Shaping Inclusive and Objective Student Character - Syaiful Rohman; Nanang Lidwan (Khazanah: Journal of Islamic Education and Science, 2026)
This study was motivated by the increasing complexity of challenges in higher education, reflected in the limited objectivity in students’ thinking and the weakening of inclusive attitudes in responding to information flow and social diversity. This condition indicated the need for an integrative approach that not only emphasized cognitive aspects but also incorporated ethical dimensions in character formation. The study aimed to analyze the synergy between scientific literacy and wasathiyah values in shaping students’ inclusive and objective character. A descriptive qualitative approach with a meta-analysis design was employed, focusing on scientific articles published between 2019 and 2025 from reputable databases. Data were collected through systematic digital documentation, while content and thematic analysis techniques were applied for data analysis. The findings revealed that scientific literacy contributed to the development of critical and objective thinking, while wasathiyah values strengthened moderate and inclusive attitudes. The integration of both aspects resulted in a more holistic student character. This study contributed to the development of an integrative conceptual framework linking epistemic and ethical dimensions in higher education and offered practical implications for character-based curriculum development.